Corilagin suppresses RANKL‐induced osteoclastogenesis and inhibits oestrogen deficiency‐induced bone loss via the NF‐κB and PI3K/AKT signalling pathways. Issue 18 (18th July 2020) - Lu, Jinwei; Ye, Chenyi; Huang, Yanyong; Huang, Donghui; Tang, Lan; Hou, Weiduo; Kuang, Zhihui; Chen, Yazhou; Xiao, Shining; Yishake, Mumingjiang; He, Rongxin
Abstract: Over‐activated osteoclastogenesis, which is initiated by inflammation, has been implicated in osteoporosis. Corilagin, a natural compound extracted from various medicinal herbaceous plants, such as Cinnamomum cassia, has antioxidant and anti‐inflammatory activities. We found that Corilagin suppressed osteoclast differentiation in a dose‐dependent manner, significantly decreased osteoclast‐related gene expression and impaired bone resorption by osteoclasts. Moreover, phosphorylation of members of the nuclear factor‐kappaB (NF‐κB) and PI3K/AKT signalling pathways was reduced by Corilagin. In a murine model of osteoporosis, Corilagin inhibited osteoclast functions in vivo and restored oestrogen deficiency‐induced bone loss. In conclusion, our findings suggested that Corilagin inhibited osteoclastogenesis by down‐regulating the NF‐κB and PI3K/AKT signalling pathways, thus showing its potential possibility for the treatment of osteoporosis.